Review Laju Penguapan Air Laut pada Kolam Garam Tertutup - Ahmad Ahdani; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
Evaporation is the process of changing liquid into vapor due to differences in vapor pressure or increased heat energy. This process is important because it forms the basis for the transfer of energy and mass from the water surface to the atmosphere and plays a role in various applications such as desalination, salt production, agriculture, liquid waste treatment, natural cooling systems, and climate studies. This study aims to determine the parameters that influence the evaporation process of seawater in a closed salt pond system based on a literature review. The methodology used is a literature study of various studies discussing the factors that influence the rate of seawater evaporation. The parameters reviewed include water and air temperature, humidity, air velocity, pressure, and radiation intensity. The review results show that temperature and radiation intensity increase the evaporation rate, while humidity and high pressure decrease it. This study provides a basis for the development of efficient and sustainable closed salt ponds.